G169(P) Management of steroid induced diabetes in children: A national perspective. (24th May 2017) - Whittle, V; Gane, J; Cheetham, T
Abstract : Aims: Hyperglycaemia is a well-recognised complication of steroid (glucocorticoid) therapy. High-dose steroids are commonly used in paediatric oncology as well as in chronic respiratory, gastrointestinal and rheumatological conditions.There are no established national or international guidelines for managing steroid induced diabetes in children. Issues such as route of insulin administration and whether a basal, prandial or a formal basalbolus regimen should be used are yet to be resolved. We aimed to gather information on how children with steroid induced diabetes are managed in the UK. Methods: Our experience is that the majority of patients with steroid induced diabetes are being managed within a paediatric oncology service and so this was the focus of this audit. We identified the 21 principle UK paediatric oncology treatment centres via the Children's Cancer and Leukaemia Group. The paediatric diabetes teams in each hospital were contacted (by phone and/or email) and information gathered about their management of children with steroid induced diabetes. Results: The diabetes teams from all 21 hospitals responded (100% response rate). Six teams (29%) treated steroid induced diabetes using 5 locally developed guidelines. The 15 teams (71%) without guidelines managed patients on an individualised basis. Treatment decisions were made by the attending diabetes consultants or on the basis of a general strategy agreed within the team. Three of the 15 teams without guidelines were developing them. Three of the 5 guidelines stated that treatment should be initiated with long acting insulin (Levemir/Glargine or Insulatard) in doses ranging from 0.2–0.7units/kg/24 hour. One guideline advocated prandial, fast-acting (Novorapid) insulin, 0.05–0.1unit/ kg as first line treatment. One guideline linked the choice of regimen to the pattern of hyperglycaemia. Eleven of the teams without guidelines stated that management reflected the preference of individual consultants, 3 teams stated they started long acting insulin and 1 expressed a preference for IV insulin as initial treatment. Conculsion: There is considerable variation in the way young people with steroid induced diabetes are managed. This may reflect the lack of a pertinent evidence base and this audit highlights the need to collect data that can be used to refine the management of this patient group.